AN ANALYSIS OF STUDENTS’ ABILITY AND DIFFICULTY IN WRITING DESCRIPTIVE TEXT AT SMP NEGERI 2 TONDANO - Balansa, Gabriela; Meity Muntuuntu; Sarah Kamagi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study is to ascertain students’ proficiency with and challenges with producing descriptive texts. Two instruments were used in the data collection process. Written texts were used as the first instrument to assess students’ descriptive writing skills, and questionnaires were used as the second instrument to assess students’ challenges. The researcher employed the Descriptive Quantitative Method to analyze the data. The twenty pupils from SMP Negeri 2 Tondano served as the research samples. The research’s conclusions showed that students’ proficiency in producing descriptive texts remained poor. Some students struggle to improve their vocabulary during the content development process, and they may still feel uncertain about selecting the right terms while writing descriptive texts. Because they struggled to come up with thoughts relevant to the issue, their overall mean score in writing was 70,3 (excellent). Occasionally, it was also discovered that certain paragraphs included just one phrase and that the paragraph’s main point was still unclear. They had some challenges with sentence construction, organization, and figuring out the general structure of descriptive texts. They struggled to put the right grammar in its proper order in grammar. Their repetitive use of terms in their writing is another effect of a limited vocabulary. They struggled with capitalization, punctuation, and spelling in mechanics. Additionally, they found it challenging to develop their ideas in the content when composing descriptive texts. In addition to a great deal of drive and critical thinking, the students require additional experience in producing descriptive texts. To help students meet their learning objectives, teachers should also provide them additional practice and examples of descriptive writings, particularly in English-related topics.